Contribution to a review of lithium-ion batteries diagnostic methods for space applications - Chapel, Lorenzo; Picot, Antoine; Lacressonniere, Fabien; Maussion, Pascal (2023 IEEE 14th International Symposium on Diagnostics for Electrical Machines, Power Electronics and Drives (SDEMPED), 2023)
Thanks to their excellent performance, lithium-ion batteries have become increasingly used in terrestrial and space applications. Despite the long lifespan, this type of battery is subject to inevitable aging dependent on electrochemical degradation phenomena. Defining a diagnostic method capable of estimating the state of health of a battery and predicting its end of life is therefore a priority to ensure proper functioning. Although considerable progress has been made in recent years in this research topic, most of the effort of the scientific community is concentrated in terrestrial applications. Of all the various existing approaches, both experimental and numerical, few are applicable within the limitations imposed by space applications. Hence, the main contribution of this paper is to provide an overview of the current state of the diagnostic methods adopted to estimate the aging of lithium-ion batteries used in satellites.